2008
DOI: 10.1002/app.29030
|View full text |Cite
|
Sign up to set email alerts
|

Post‐oligomerization of α‐olefin oligomers: A route to single‐component and multicomponent synthetic lubricating oils

Abstract: This article describes a synthetic route to single‐component and multicomponent base stocks for synthetic lubricated oils. The synthesis was carried out in two stages. First, oligomers of α‐olefins (1‐hexene, 4‐methyl‐1‐pentene, and 1‐decene) were prepared via reactions catalyzed by metallocene catalysts. The distribution of the oligomers with respect to their oligomerization number could be controlled by the reaction temperature. The oligomer mixtures were then fractionated, and the lightest components, dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…The presence of bulky alkyl or aryl substituents in the cyclopentadienyl rings resulted in decreasing activities of metallocenes and an increased content of higher oligomers; increasing the number of alkyl substituents entailed the same effect. The early results in the study of the oligomerization of α-olefins in the presence of zirconocenes 1 and 8 at Al MAO /Zr~200 [47] were complemented substantially by Nifant'ev et al [91], who established that under these conditions, the products of side reactions (2-alkenes and alkanes) typically exceeded 10 wt %. Therefore, bis-cyclopentadienyl complexes at high Al MAO /Zr ratios have poor prospects for the oligomerization of α-olefins.…”
Section: Metallocene-catalyzed Oligomerization Of α-Olefins and Activmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bulky alkyl or aryl substituents in the cyclopentadienyl rings resulted in decreasing activities of metallocenes and an increased content of higher oligomers; increasing the number of alkyl substituents entailed the same effect. The early results in the study of the oligomerization of α-olefins in the presence of zirconocenes 1 and 8 at Al MAO /Zr~200 [47] were complemented substantially by Nifant'ev et al [91], who established that under these conditions, the products of side reactions (2-alkenes and alkanes) typically exceeded 10 wt %. Therefore, bis-cyclopentadienyl complexes at high Al MAO /Zr ratios have poor prospects for the oligomerization of α-olefins.…”
Section: Metallocene-catalyzed Oligomerization Of α-Olefins and Activmentioning
confidence: 99%
“…As compared with zirconocene 1, in the presence of the 6 dimer of sterically hindered olefin, 3-methylbut-1-ene was obtained with an average yield; substituted silanes and allylthiophenes also formed vinylidene dimers [41] (Scheme 2b). Note that the zirconium pre-catalysts 7 [44][45][46], 8 [47], 3 [48], 9 [49,50], and 10 [51] and the hafnium complex 11 [48], studied previously in α-olefin dimerization, were less active and selective in comparison with 6.…”
Section: Group 4 Metallocene-catalyzed Synthesis Of Methylenealkanesmentioning
confidence: 99%
“…This supposition can be deduced from the greatly decreasing rates of oligomerization in batch oligomerization reactions [31]. The TOFs in batch reactors at longer times are more than two orders of magnitude less (10 −4 -10 −3 s −1 at temperatures below 170 • C) than the initial rates [31,47,48]. Therefore it is difficult to establish quantitative relationships between site density and oligomerization rate, although a qualitative connection undoubtedly exists, as shown in Fig.…”
Section: Lifetime Studies Of Ps-dvbsmentioning
confidence: 91%
“…In 2009, Kissin et al reported oligomerisation of 1-hexene and separately 1-decene using nBuCp 2 ZrCl 2 and MAO with Al/Zr molar ratio of 200. 38 They have demonstrated that by changing the temperature from 70 C to 90 C, the percentage of dimer increased from 60% to 71%. The dimers obtained from two cases were further polymerised using AlCl 3 -supported, EtAlCl 2 -supported and silica-supported EtAlCl 2 , and the products were analysed using gas chromatography.…”
Section: Metallocenes Catalystsmentioning
confidence: 99%
“…In 2009, Kissin et al . reported oligomerisation of 1‐hexene and separately 1‐decene using nBuCp 2 ZrCl 2 and MAO with Al/Zr molar ratio of 200 . They have demonstrated that by changing the temperature from 70°C to 90°C, the percentage of dimer increased from 60% to 71%.…”
Section: Introductionmentioning
confidence: 99%